Administration of Public Universities in Nigeria: Problems and Solutions - Ogunode Niyi Jacob (Jurnal Sinestesia, 2020)
Public universities in Nigeria were established to provide post-secondary education for the Nigerian citizens. The Nigerian public universities were among the best in the world before but the situation has changed. The performance of Nigerian public universities is not encouraging. Many problems have been identified as responsible. Problems of poor administration of public universities have been identified by different scholars as a problem facing the public universities in Nigeria. This article discusses the problems facing the administration of public universities in Nigeria. Secondary data were used in the article. The secondary data were sourced from online and print resources. The article identified; inadequate funding, inadequate academic staff, inadequate infrastructural facilities, brain-drain, insecurity, strike actions, corruption, inadequate data to plan, political influence and weak administrators as the problems facing the administration of public universities in Nigeria. To solve the problems, the following were recommended: increase in the funding of public universities, employment of more academic staff, provision of adequate infrastructural facilities, ensure adequate security, fight all forms of corruption, provision of adequate data, grant autonomy to all public universities, motivate all the academic staff, improve on data generation and distribution, implement all agreement reached with union groups in the public universities and appointment of competent administrators for the public universities in Nigeria.